Ponatinib in the treatment of patients with chronic myeloid leukemia and increased cardiovascular risk: A review of management strategies - Tomasz Sacha; Katarzyna Krawczyk (Hematology, Transfusion and Cell Therapy)
The introduction of tyrosine kinase inhibitors has revolutionized the treatment of chronic myeloid leukemia vastly improving the prognosis and clinical outcome of most patients. It was estimated that approximately 40–50 % of patients treated with imatinib will require treatment with a second-generation or third-generation tyrosine kinase inhibitor to achieve an optimal response. The treatment duration, increased patient survival, and aging of the population receiving tyrosine kinase inhibitors raise concerns as to long-term toxicities, such as an elevated cardiovascular risk and a higher rate of comorbidities. Ponatinib is a highly potent third-generation tyrosine kinase inhibitor that was shown to be effective in patients with a wide range of ABL mutations, including T315I. The use of ponatinib is associated with significant vascular toxicity, including peripheral arterial occlusive disease, ischemic heart disease, cerebrovascular accidents, and venous thromboembolism. This review discusses the vascular toxicity of ponatinib and presents a comprehensive panel of tests for the evaluation of patients requiring ponatinib therapy. Moreover, the management of patients with cardiovascular risk factors who receive ponatinib is discussed. Finally, the strategy for establishing the optimal dose of ponatinib in patients with chronic myeloid leukemia is described.